2010
DOI: 10.1007/s12630-010-9418-x
|View full text |Cite
|
Sign up to set email alerts
|

Brief review: Anesthetic neurotoxicity in the elderly, cognitive dysfunction and Alzheimer’s disease

Abstract: Purpose Postoperative cognitive decline in the elderly has emerged as a major health concern. In addition, there is a growing interest in the potential relationship between general anesthetic exposure and the onset and progression of Alzheimer’s disease (AD). The available evidence of a possible association between anesthesia, surgery, and long-term cognitive effects, including AD, deserves consideration. In this review, we summarize the evidence for anesthesia-induced neurotoxicity in the elderly, while highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 68 publications
3
69
0
2
Order By: Relevance
“…It operates in two types of receptors, the Trk, expressed in normal conditions and that promotes proper homeostasis and synaptogenesis and the p75NTR receptor which has a higher binding specificity to the BDNF precursor (pro-BDNF). [19] Consequently, there is an accumulation of pro-BDNF in the synaptic clefts with higher binding to p75 NTR receptors, which leads to caspase-3 activation, decreased formation of dendrites and apoptosis. The inhibition of BDNF formation by the anesthetics (especially propofol and isoflurane) also acts indirectly in the neural cell cytoskeleton, pro- This article is available at: www.intarchmed.com and www.medbrary.com 6 moting the destabilization of the actin, one of its structural components, and reducing its survival.…”
Section: Discussionmentioning
confidence: 99%
“…It operates in two types of receptors, the Trk, expressed in normal conditions and that promotes proper homeostasis and synaptogenesis and the p75NTR receptor which has a higher binding specificity to the BDNF precursor (pro-BDNF). [19] Consequently, there is an accumulation of pro-BDNF in the synaptic clefts with higher binding to p75 NTR receptors, which leads to caspase-3 activation, decreased formation of dendrites and apoptosis. The inhibition of BDNF formation by the anesthetics (especially propofol and isoflurane) also acts indirectly in the neural cell cytoskeleton, pro- This article is available at: www.intarchmed.com and www.medbrary.com 6 moting the destabilization of the actin, one of its structural components, and reducing its survival.…”
Section: Discussionmentioning
confidence: 99%
“…Patients over the age of 65 are at a particularly high risk of postoperative confusion (delirium) and cognitive disorders (PCD -Postoperative Cognitive Dysfunction) [29,30]. The guidelines presented in this paper set out the general rules of anaesthesia in elderly patients.…”
Section: Specific Postoperative Problemsmentioning
confidence: 99%
“…Although these anesthetics are generally considered to be safe in clinical anesthesia, several studies have shown that these agents can cause cell damage, neurodegeneration or postoperative cognitive decline Wang et al, 2009;Wei and Xie, 2009;Zhu et al, 2010;Bittner et al, 2011;Campbell et al, 2011;Zou et al 2011). The common inhalational anesthetic isoflurane induces cytotoxicity in both a concentration-and time-dependent manner in different types of cultured cells.…”
Section: Introductionmentioning
confidence: 99%